The Art of Reading the Financial Pulse: Activity vs Profitability - Syaifuddin, Dedy Takdir; Machmud, Mulyana; Hartati, Hartati (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study analyzes the influence of activity ratio and profitability on the financial performance of PT. PLN (PERSERO) UP3 PAREPARE CITY for the 2021-2023 period, using quantitative descriptive analysis with interactive data visualization. The results showed mixed performance dynamics: Total Asset Turnover was stable but suboptimal (0.6), Receivable Turnover Ratio increased gradually (15 to 17), Inventory Turnover fluctuated significantly (78, 186, 83), Fixed Asset Turnover stagnated (0.6), Gross Profit Margin was positive but decreased at the end (119.1%, 123.1%, 102.5%), Net Profit Margin decreased drastically (271.4%, 266.9%, 71.3%), and Return On Assets was strong at the beginning but decreased significantly (152.8%) %, 162.1%, 45.0%). The analysis uncovers areas that require strategic attention, particularly in asset optimization and profitability, considering the importance of continuous adaptation in operational and financial strategies to maintain strong performance amid changing market dynamics.